2018
DOI: 10.1080/14767058.2018.1427719
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cerclage in twin pregnancies on preterm birth rate before 32 weeks

Abstract: Cerclage in twin pregnancies significantly decreased the rate of spontaneous preterm birth <32 weeks compared to expectant management. However, when stratified by cerclage indication, this decrease in primary outcome only remained significant in the group with cervical dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…Other studies have also drawn similar conclusions that cervical cerclage including EC in twin pregnancies significantly decreased the rate of spontaneous preterm births [ 8 , 19 ]. The reason for these conflicting results regarding the efficacy of cerclage in twin pregnancies might be due to different surgical techniques and management protocols used in different institutions [ 27 ]. In our study, the rate of preterm birth and the rate of VLBWI or ELBWI in twin pregnancies were not increased compared to the rates in singleton pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also drawn similar conclusions that cervical cerclage including EC in twin pregnancies significantly decreased the rate of spontaneous preterm births [ 8 , 19 ]. The reason for these conflicting results regarding the efficacy of cerclage in twin pregnancies might be due to different surgical techniques and management protocols used in different institutions [ 27 ]. In our study, the rate of preterm birth and the rate of VLBWI or ELBWI in twin pregnancies were not increased compared to the rates in singleton pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that EC in twin pregnancies improved neonatal outcomes when compared to expectant management [ 27 29 ]. Another study also concluded that EC for cervical insufficiency in twin pregnancies and in singleton pregnancies contributed to a good perinatal prognosis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in cases when the cervix is opened, cervical stitching is almost the only treatment option (compared to absolute bed rest). Although no randomized control trial study has been performed specifically on multiple pregnancies, the results from retrospective studies show that cervical lifecycle in multiple pregnancies helps prolong pregnancy by 7.3 days to 91 days [7] [14] [15]. In the trend of increasing fertility support, the rate of multiple pregnancies is also increasing.…”
Section: Discussionmentioning
confidence: 99%
“…preterm birth,Emergency cervical cerclage reduces preterm birth, provides prolonged gestational weeks, and reduces neonatal mortality and loss rates. SOGC [4] recommends emergency cervical cerclage in a singleton pregnant cervix less than 4cm without contractions.The Han et al [5] retrospective study analyzed the prolonged pregnancy interval of 5-7 weeks after cervical dilation> 1cm compared to the conservative treated group.Emergency cervical cerclage is an active treatment that extends gestational weeks and increases neonatal survival, However,premature fetal membrane rupture occurs in 4%-9% postoperative cases,when the amniotic cavity intrauterine infection is present, the effect of cerclage decreases signi cantly [6].Several studies have shown that the amniotic sac is located beyond external os and that the cervix dilation of 1.5cm is an independent risk factor for failure after cerclage [7],The Baryk M et al [8] study evaluated emergency cervical cerclage with less than 28 weeks of premature birth at 75/252 (29.7%),In this study, 106 patients underwent emergency cervical dilation and amniotic protrusion, and 39 had sPTB less than 28 weeks with an incidence of 36.8%,Higher than the above study may be related to a higher proportion of cervical expansion greater than 4cm (18 cases). Emergency cervical cerclage has a positive effect on pregnancy outcome with cervical dilation> 4cm, less than spontaneous prematurity of 18/37 (46.2%) at 28 weeks, prolonged gestational interval of 4.43 (3.43,7.00)…”
Section: Tablementioning
confidence: 99%